As calhas de ferro Walter MacFarlane’s: a documentação dos ornamentos metálicos remanescentes nos bairros Reduto e Nazaré em Belém/PA como subsídio de preservação - RAIOL, Marcela Cristiane Sousa (2019)
Due to the great investments made in the city during the 19th century, Belém (PA, Brazil) went through a period of intense modernization, where products were imported from Europe in order to satisfy the wishes of the local bourgeoisie. Among these products were the architectural elements of iron used in façades, which came to meet the needs of the urbanization plan proposed by Antônio Lemos. The ornamental rainwater heads and railings of Walter MacFarlane's company were part of these imported items and can be seen today in the historic center and its surroundings. Of great aesthetic and functional importance, the iron rainwater heads and railings are historical witnesses of means of production and the development of the city, but they are in potential risk of disappearance, mainly because they are elements that can easily be replaced or removed. Therefore, the present research aims to document the remaining rails in the neighborhoods of Nazaré and Reduto, located in the vicinity of the Historical Center of Belém. 256 Walter MacFarlane's iron head water and ralings were documented, of different types, identified from the models presented in the company's sales catalog. Most railings presented some type of damage, such as gaps, corrosion and their anomalies, as well as contamination by biological agents, contemporary interventions in gutter structure and others.